Daring the Difference : The Three L's of Women's Empowerment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
Daring the Difference: The Three L's of Women's Empowerment. Speech delivered by IMF Managing Director Christine Lagarde in May, 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States